2009
DOI: 10.1186/1472-6947-9-9
|View full text |Cite
|
Sign up to set email alerts
|

The influence of context and process when implementing e-health

Abstract: BackgroundInvesting in computer-based information systems is notoriously risky, since many systems fail to become routinely used as part of everyday working practices, yet there is clear evidence about the management practices which improve the acceptance and integration of such systems. Our aim in this study was to identify to what extent these generic management practices are evident in e-health projects, and to use that knowledge to develop a theoretical model of e-health implementation. This will support t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 15 publications
3
51
0
Order By: Relevance
“…Of the 12 articles reviewed, five gave an explicit or implicit definition of ehealth similar to WHO14 and ECIS,15 22 28 55–57 one provided a list of functionality and resource requirements58 while six defined a specific ehealth application but not ehealth itself 26 30 59–62. Although shared care is the basis for inclusion, only one paper included a definition: ‘establishing coherent treatment of the patient through close coordination and cooperation across care sector boundaries’60 while Melby et al 61 offered ‘integrated’ or ‘seamless’ care as alternative terms.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 12 articles reviewed, five gave an explicit or implicit definition of ehealth similar to WHO14 and ECIS,15 22 28 55–57 one provided a list of functionality and resource requirements58 while six defined a specific ehealth application but not ehealth itself 26 30 59–62. Although shared care is the basis for inclusion, only one paper included a definition: ‘establishing coherent treatment of the patient through close coordination and cooperation across care sector boundaries’60 while Melby et al 61 offered ‘integrated’ or ‘seamless’ care as alternative terms.…”
Section: Resultsmentioning
confidence: 99%
“…Three ehealth research themes were identified with a shared care focus: Telemedicine57 58 Generalised ehealth implementation22 56 59 Electronic health records26 28 30 55 60–62 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, in these cases even excellent eHealth-based customer care initiatives are likely not to be accepted by health care providers, unless other, more civilized barriers against patient (and expenditure) overload are provided to replace "good old" bureaucratic bothers and uncomfortable access! In other words, when we study health care strategies and eHealth solutions from the point of view of different stakeholders, it becomes apparent that innovation processes, to be successfully put in practice, must be founded on a sound awareness of the many, complex and contrasting interests hidden in the health care system they are faced with (Boddy et al 2009 ) .…”
Section: Health Care Professionals and Patients •mentioning
confidence: 98%
“…The introduction of technology in healthcare system introduce a number of changes to overall healthcare delivery, including the context where care is delivered and the way in which it is delivered (Boddy et al, 2009). This can result in factors contributing to conflict among its users and contradiction in overall goals ( May, 1993 However, to apply this approach appropriately, IS innovation based services such as telehealth and electronic records have to be seen as an extension of a healthcare social system that spans across time and space.…”
Section: Conceptualising Context As Healthcare Social Systemmentioning
confidence: 99%